Influence of X-rays on the thermal properties of poly(methyl methacrylate) - Gil, Małgorzata; Wójcik, Grzegorz; Szewczyk, Kamil; Pędzisz, Janusz; Kopeć, Jarosław; Czyżewska, Lidia; Walewski, Aleksander; Gorgol, Andrzej; Podkościelny, Wiesław; Mergo, Paweł (Photonics Letters of Poland, 2014)
The aim of this work was to determine the influence of X-rays, on the thermal properties of poly(methyl methacrylate), which is typically used as a material in technology of polymer optical fibers. The thermal properties of the optical polymer (PMMA - poly(methyl methacrylate) after the radiation were evaluated using Thermogravimetry analysis (TGA). Full Text: PDF References O. Ziemann, et al., POF Handbook ? Optical Short Range Transmission Systems. 2nd ed. 2008, Berlin: Springer. R. L. Clough and S. W. Shalaby, "Radiation effects on polymers", American Chemical Society, Washington (1991). CrossRef T. Coffey at al., "Characterization of the effects of soft X-ray irradiation on polymers", Journal of electron spectroscopy and related phenomena 122, 65-78 (2002). CrossRef T. Sasuga et al., "Effects of ion irradiation on the mechanical properties of several polymers", Radiation physics and chemistry 37, 135-140 (1991). CrossRef H. Henschel, M. Wittenburg, F. Wulf, "Fiber Optic Radiation Sensing Systems for TESLA", TESLA Report, 2000-2026 (2000). DirectLink H. Yoshida, T. Ichikawa, "Temperature effect on the radiation-degradation of poly(methyl methacrylate)", Radiation Physics and Chemistry 46, 921 (1995). CrossRef